Perturbation of the tRNA Tertiary Core Differentially Affects Specific Steps of the Elongation Cycle - Pan, Dongli (American Society for Biochemistry and Molecular Biology, 2008)
The tRNA tertiary core region is important for both tRNA stability and activity in the translation elongation cycle. Here we report the effects of mutating each of two highly conserved base pairs in the tertiary core of Phe-tRNA(Phe), 18-55 and 19-56, on rate and equilibrium constants for specific steps of this cycle, beginning with formation of aminoacyl-tRNA·EF-Tu·GTP ternary complexs and culminating with translocation of A-site-bound peptidyl-tRNA into the P-site. We find that codon-dependent binding of aminoacyl-tRNA to the A/T-site and proofreading of near-cognate tRNA are sensitive to perturbation of either base pair; formation of the ternary complex and accommodation from the A/T to the A-site are sensitive to 18-55 perturbation only, and translocation of peptidyl-tRNA from the A- to P-site is insensitive to perturbation of either. These results underline the importance of the core region in promoting the efficiency and accuracy of translation, and they likely reflect different requirements for structural integrity of the core during specific steps of the elongation cycle.